Changes in Musculoskeletal Discomfort and Postural Alignment According to the Height of the Worktable When VDT Activities were Performed by Patients in a Wheelchair with C6 and T6 Spinal Cord Injuries - Bo-Ra Kang,; Jeong-Weon Lee, (International Journal of Innovative Research in Medical Science, 2021)
Purpose: This purpose of the study was to identify the effects of computer worktable heights on musculoskeletal changes in the neck and upper extremities and postural alignment in patients with C6 and T6 level spinal cord injuries. Materials and Methods: The participants in the present study were patients diagnosed with AIS A. The level of the worktable was set 5 cm below the elbow, at elbow level, and 5 cm above elbow level. Subjective musculoskeletal discomfort (Borg-RPE) was measured at the end of the experiment. To compare the side posture for the wheelchair axle, patients with C6 and the T6 injuries were selected to measure the angle of the centerline for the axle, the tip of the chin, and the postural change for the tragus of the ear. Results: First, in the patient with C6 injuries, the Borg-RPE scores decreased when the worktable height was 5 cm above the elbow, whereas, in the patient with T6 injuries, the Borg-RPE scores decreased when the worktable height was decreased. Second, in the patient with C6 injuries, the chin tip and tragus of the ear were close to the center of the wheelchair when the height of the worktable was 5 cm above the elbow in the lateral position. In the patient with T6 injuries, there was no difference in lateral posture according to the height of the worktable. Conclusion: To reduce musculoskeletal system discomfort in patients during video display terminal (VDT) work, it is necessary to set the worktable height higher than the elbow standard for patients with C6 injuries and lower than elbow height for patients with T6 injuries. In the case of posture change, in the patient with C6 injuries, the higher the worktable height, the more the neck and head changed from forward flexion to a neutral posture.